Use of DPSIR Framework to Analyze Water Resources in Qatar and Overview of Reverse Osmosis as an Environment Friendly Technology. Issue 4 (11th October 2018) - Ashfaq, Mohammad Y.; Al‐Ghouti, Mohammad A.; Qiblawey, Hazim; Zouari, Nabil; Rodrigues, Debora F.; Hu, Yandi
Abstract : Qatar and other countries of Gulf Cooperation Council are among the most water scarce countries in the world and are being characterized as "high‐water risk" countries by Water Resource Institute. Therefore, it is important to implement sustainable water resource management that encompass economic, societal, and environmental aspects. In this review article, the Driver‐Pressure‐State‐Impact‐Response framework was used to analyze the water resource system in Qatar in terms of drivers, pressures, change in state, impacts, and responses. It was noted that both economic and population growth together with unsustainable water consumption are major driving forces that are pressurizing the Qatar's water resources (desalinated seawater and renewable groundwater). Currently, desalination plants using Multi‐Stage Flash (MSF) techniques are predominantly being used to meet the rising water demands. However, widespread use of MSF techniques poses several environmental and economic impacts. Therefore, in addition to other management and corrective measures, reverse osmosis (RO) technique has also been suggested to be utilized in desalination industry as a "response" to mitigate those impacts. Since, the performance of RO is mainly affected by biofouling and mineral scaling, the paper also highlights the recent materials (polymers and nano‐materials) used to tackle these problems. © 2018 American Institute of Chemical Engineers Environ Prog, 38:e13081, 2019